Economical and friendly products innovation / Nur Fatiyah Rosian … [et al.] - Rosian, Nur Fatiyah; Mislan, Ayuffeirah; Zakaria, Noorul Huda; Abdullah, Nur Solihah Khadhiah; Zakirai@ Zakaria, Norlida; Johari, Rozarina (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Banners, buntings and posters can be very useful in communicating message. Although there have been multimedia to replace these conventional communication, promoting information with banners, buntings and posters still have been used widely as an excellent way to convey a message or promoting a product due to the highly impact and inexpensive means of marketing. However, where do all these materials go after delivering the message? We often have discarded the banners, buntings and posters after we use them. However, there are several more ecologically friendly options than throwing them in the trash, where all these materials should be recycled. The purpose of this project is to recycle these materials to become soft furnishing such as shopping bag, apron, office partition, pencil case, kitchen curtain, hanging rack, picnic mat and also table cloth. All these products are suitable for office and home use. It is an economic and sustainable project as it helps to prevent environmental pollution as well as generates new source of income especially to low income group of the rural community. Besides that, this project can give a high awareness among rural community.